2017
DOI: 10.1055/s-0037-1604161
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Wound Vacuum Therapy after Cesarean Section to Prevent Wound Complications in the Obese Population: A Randomized Controlled Trial (the ProVac Study)

Abstract: Objective The objective of this study was to perform a randomized controlled feasibility trial investigating negative pressure wound therapy (NPWT) system versus a standard postcesarean wound care (WC) on the development of a postoperative surgical site infection (SSI) and/or a wound dehiscence in obese women. Study Design This is a randomized controlled feasibility trial of obese women undergoing an unscheduled cesarean delivery. Women with an initial body mass index ≥ 30 kg/m2 who were ≥ 4 cm dilated were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 11 publications
0
56
0
Order By: Relevance
“…Eventually, a total of 40 relevant articles [ 10 , 11 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] were included in the current systematic literature review whereas 21 articles provided data for meta-analysis. Six studies regarding skin incision [ 24 , 26 , 27 , 31 , 33 , 42 ] and 9 studies regarding drainage [ 21 , 22 , 23 , 24 , 25 , 27 , 32 , 35 , 46 ] were performed in meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eventually, a total of 40 relevant articles [ 10 , 11 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ] were included in the current systematic literature review whereas 21 articles provided data for meta-analysis. Six studies regarding skin incision [ 24 , 26 , 27 , 31 , 33 , 42 ] and 9 studies regarding drainage [ 21 , 22 , 23 , 24 , 25 , 27 , 32 , 35 , 46 ] were performed in meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A meta-analysis of six studies showed that suturing reduces the risk of wound complications by 34% [65] in subcutaneous tissue that is thicker than 2 cm. A randomized study of 1082 women undergoing a caesarean section treated with antibiotic prophylaxis for more than 60 min from the skin incision, with the skin washed with an alcoholic chlorhexidine solution, and sutured subcutaneous tissue if its thickness was greater than 2 cm, as well as skin closed with sutures instead of staplers, showed a significant reduction in the risk of complications in the postoperative wound, regardless of the method of The results were stable after omitting one study at a time, i.e., the study by Hussamy et al [43] first, then a study by Ruhstaller et al [37], then a study by Wihbey et al [39], and then a study by Tuuli et al [47]. When the study by Hylding et al [44] was omitted, the results changed and were not significant (OR = 0.84 95% CI 0.65-1.08, p = 0.17).…”
Section: Discussionmentioning
confidence: 97%
“…The Tuuli et al 26 study included only obese patients with BMI ≥30 kg/m 2 , whereas Chaboyer et al 22 defined obesity as BMI ≥25 kg/m 2 , which could somewhat account for differences in outcomes between the two studies in meta-analysis 2. For further comparison, in meta-analysis 1, Gunatilake et al 13 defined obesity as BMI ≥35 kg/m 2 and Ruhstaller et al 20 defined obesity as BMI ≥30 kg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Health economic data for ciNPT use is limited. While only two studies were identified in the literature search, they provided differing conclusions [14,28]. Additionally, since 2009, only three other studies examining the health economics of ciNPT use have been published [33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies identified from the literature search examined the economic impact of ciNPT use in patients at high risk for developing SSIs (Table 3) [14,28]. The Kwon et al study indicated a cost savings of $6,045 in ciNPT patients; however, Ruhstaller et al found an increase in patient costs ($10,300) in the ciNPT patient group [14,28]. More economic studies are needed to fully assess the potential economic benefit of ciNPT use.…”
Section: Economic Analysis Of Published Clinical Studiesmentioning
confidence: 99%